EFFECT OF LERAK (SAPINDUS RARAK) EXTRACT IN HIGH ROUGHAGE DIET ON RUMEN MICROBIAL PROTEIN SYNTHESIS AND PERFORMANCE OF SHEEP - Elizabeth Wina; Stefan Muetzel (Indonesian Agency for Agricultural Research and Development, 2020)
Secondary compounds containing plant extract as feed additive may improve the performance of livestock consuming high roughage diet. An in vivo trial was conducted to investigate the effect of Sapindus rarak extract (SRE) on ruminal fermentation products, microbial protein synthesis, and growth performance of sheep. Sheep (male, 28 heads) fed high roughage diet were arranged in a completely randomized design with four treatments: addition of SRE to the diet at 0, 4, 8 and 12 g head-1 day-1. The experiment was conducted for 105 days with 2 weeks adaptation period. At the end of the experiment, total faeces was collected for 1 week and rumen liquor was taken. Variables measured were ruminal fermentation products, microbial protein synthesis, daily intake, digestibility, N retention, body weight, and average daily gain. Protozoal numbers were significantly decreased with increasing SRE dose. The ruminal NH3 concentration tended to reduce by SRE addition (P = 0.06). SRE significantly increased propionate and efficiency of microbial protein synthesis from 6.4 to 10.5 g N kg-1 DOMR. SRE significantly improved average daily gain of sheep during the first 70 days of experiment without affecting intake and digestibility. SRE did not alter carcass percentage but tended to lower pancreas and liver weights (P<0.1). In conclusion, SRE has a significant role in partially defaunated rumen microflora, hence, increased microbial protein synthesis and propionate production in the rumen. Addition of SRE is useful to increase daily gain of sheep fed high roughage diet in 70 days of feeding.